Undergraduate research and the academic librarian : case studies and best practices. Volume 2 - Hensley, Merinda Kaye; Fargo, Hailley; Davis-Kahl, Stephanie (Chicago, Illinois : Association of College and Research Libraries, a division of the American Library Association, 2023)
"Undergraduate research is often conflated with standard end-of-semester research papers, featuring APA style bibliographies and a certain number of sources. But in fact, undergraduate research is one of several high-impact educational practices identified by George Kuh and the Association of American Colleges & Universities, and is increasingly seen as a vital part of the undergraduate experience. Research helps students connect the dots between their interests, general education courses, writing requirements, and major coursework, and increases learning, retention, enrollment in graduate education, and engagement in future work. In 25 chapters featuring 60 expert contributors, Undergraduate Research and the Academic Librarian examines how the structures that undergird undergraduate research, such as the library, can become part of the core infrastructure of the undergraduate experience. It explores the strategic new services and cross-departmental collaborations academic libraries are creating to support research: publishing services, such as institutional repositories and undergraduate research journals; data services; copyright services; poster printing and design; specialized space; digital scholarship services; awards; and much more. These programs can be from any discipline, can be interdisciplinary, can be any high-impact format, and can reflect upon an institution's own history, traditions, and tensions. As higher education becomes more competitive--for dollars, for students, for grant money, for resources in general--institutions will need to increase their development of programs that provide the experiential and deep learning, and increased engagement, that research provides. The scholarly and extracurricular experiences of college are increasingly becoming a major part of marketing college education. Beyond the one-shot, beyond course-integrated instruction, Undergraduate Research and the Academic Librarian is a detailed guide to how librarians can help students go beyond a foundation of information literacy toward advanced research and information management skills"--provided by publisher.
Foreword. Adding value to the undergraduate research experience / George D. Kuh -- Beyond embedded librarianship: co-teaching with faculty to integrate digital scholarship in undergraduate research / Sarah Clayton and Jeffrey M. Widener -- The cooperation of many minds: cultivating the undergraduate researcher in the humanities and social sciences through team-based curricular design / Susette Newberry -- A triumph, a fail, and a question: a pilot approach to student-faculty-librarian research collaboration / Missy Roser and Sara Smith -- Framing information literacy as scholarly practice with undergraduate student journals: a grassroots approach / Deena Yanofsky, Michael David Miller, and Urooj Nizami -- Building relationships, advancing services: piloting open conference systems with the Indiana University undergraduate research conference / Shayna Pekala and Jane Rogan -- Doing the honors: designing a curriculum for a year-long thesis project / Amanda Piekart-Primiano, Matthew Regan, and Lily Sacharow -- Dreaming big: library-led digital scholarship for undergraduates at a small institution / Janelle Wertzberger and R.C. Miessler -- Engaging in the undergraduate researcher writers' process: creating a thesis writers' bootcamp / Katie Harding and Lora Leligdon -- Engaging our student partners: student leadership in a library-initiated experiential learning project / Michelle Reed, Philip Duncan, and Germaine Halegoua -- Freshman framework: collaboratively developing a set of required instructional modules for freshman research scholars / Matt Upson, Tim O'Neil, and Cristina Colquhoun -- From the archives to the institutional repository: a collaborative approach to research and publishing for undergraduate creative writers / Brandon T. Pieczko and Laura MacLeod Mulligan -- Harnessing the winds: collaboration and the Aeolus undergraduate research journal / Alyson Gamble, Amelia Kallaher, Neal Lacey, Alexandra Maass, Caitlyn Ralph, Tyrone Ryba, and Mai Tanaka -- Image of research: celebrating and sharing undergraduate work / Michelle Reed and Merinda Kaye Hensley -- Impact outside the classroom: preparing undergraduate researchers for success / Lisa Becksford, Kyrille Goldbeck DeBose, and Carolyn Meier -- Informal learning teams and the digital humanities: a case study of faculty/librarian collaboration / Lora L. Smallman and Jessica DeSpain -- Landscape architecture, embedded librarianship, and innovation with special collections: historic landscapes research with primary sources by University of Arkansas undergraduates / Joshua C. Youngblood -- Mentoring a peer: a feminist ethic for directing undergraduate humanities research / Amy Hildreth Chen and Kathryn Ross -- Re-imagining Furman engaged: transformation through a library partnership / Andrea M. Wright and John G. Kaup -- Connecting students to the research lifecycle and to each other: planning an event to support undergraduate journal publishing / Heather Buchansky and Graeme Slaght -- Reward research, benefit all: the case of the library undergraduate research award at Kennesaw State University / Ariel Turner and Aajay Murphy -- Sharing student research: student colloquia at University of South Florida St. Petersburg / Camielle Crampsie and Kaya van Beynen -- Teaching integrity in empirical economics: the pedagogy of reproducible science in undergraduate education / Norm Medeiros and Richard J. Ball -- The honors colloquium at QCC: a decade of excellence / Dale LaBonte, Denise Cross, Fyiane Nsilo-Swai, Matt Bejune, Susan McPherson, and Tiger Swan -- Transcribing women's diaries in the digital world / Elizabeth A. Novara and Jessica Enoch -- Undergraduate research in the archives: a case study of collaborative teaching and dissemination of aerospace history / Tracy B. Grimm.
Includes bibliographical references.
Description based on online resource ; title from PDF title page (Ebook Central, viewed February 13, 2024).
Keywords: Academic librarians -- Relations with faculty and curriculum; Academic libraries -- Vocational guidance; Undergraduates -- Research; Undergraduates -- Research -- Case studies; Undergraduates -- Services for; Libraries and publishing